(untitled) (Revista Torreón Universitario, 2019)
Dear readers, we put in your hands one more copy of the Torreón Universitario Magazine, which aims to disseminate the generation and transfer of knowledge with the scientific research works of expert researchers, both nationally and internationally, in order to improve the quality, type and focus of the same. This journal has been awarded as part of the IX Edition of the National Innovation Award by the Nicaraguan Council of Science and Technology (CONICYT) in 2015 through the Vice Presidency of the Republic, for its effort to raise the quality and application of the criteria of the Regional Online Information System for scientific journals in Latin America. the Caribbean, Spain and Portugal (LATINDEX) and to achieve visibility of Nicaragua’s scientific production in Latin American Journal Online (LAMJOL). At the same time, it is indexed in two international catalogues LATINDEX and CAMJOL, with a presence on the Rev Portal